FROM SCHOOLBOY INTO FULL-TIME ATHLETE: EXPLORING SLEEPING HABITS AND DIETARY INTAKE OF JUNIOR FOOTBALL PLAYERS IN EAST JAVA - Fitria, S.Gz, M.Sc, Anisa Lailatul; Salsabila, Qizza; Pribadi, Heri Purnama; Kusumawardhani, Mahda Putri; Ramadhan, Sasha Anggita; Azzahra, Aprillia; Diana, Rian; Rifqi, Mahmud Aditya; Pratiwi, Azizah Ajeng; Atmaka, Dominikus Raditya; Simangunsong, Tiara Tivany; Agustin, Asri Meidyah; Wahyudi, Nanang Tri (Media Gizi Indonesia, 2025)
Junior football players often encounter difficulties in managing their sleep and dietary patterns. At the same time, they need to balance their time between scheduled school activities and training sessions. This dual responsibility can sometimes make junior athletes susceptible to sleep and dietary issues, potentially affecting their performance. This study aimed to examine the sleep patterns and dietary intake of football players across different age groups at a football club in East Java. We compared the sleep patterns and dietary intake of players in the U18 (n=18), U16 (n=13), and U14 (n=8) categories. Data were collected through interviews using validated questionnaires. Dietary intake was assessed with a semi-quantitative Food Frequency Questionnaire (SQ-FFQ). Sleeping quality and quantity were assessed using structured questionnaire adapted from Pittsburgh Sleeping Quality Index (PSQI). The results showed no statistically significant differences in the quality or quantity of sleep across all groups (p > 0.05). However, a trend suggested that U18 players had slightly better sleep quality and quantity compared to the other groups. In contrast, the U18 group demonstrated significantly lower energy intake than the other groups (p = 0.000). The U16 group exhibited the best energy and nutrient intake among all age categories. In conclusion, older and younger player groups tend to overlook dietary patterns, while their sleep patterns remain relatively consistent.